TINGKAT KECEMASAN SISWA DALAM MENGHADAPI UJIAN SEKOLAH DITINJAU DARI JENIS KELAMIN, JURUSAN DAN DAERAH ASAL SERTA IMPLIKASI - Sari, Astri Widya; Mudjiran, Mudjiran; Alizamar, Alizamar (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2017)
This research based on phenomenon that students encounter high level of anxiety in facing Ujian Sekolah (US) such as heart palpitations while following debriefing ujian sekolah, sweat and cold hands while doing ‘try out’ for US and panic easily about changes of the information regarding US. The research purpose to reveal student’s anxiety level in facing US reviewed by gender, major, ancestry and the difference, also the interaction between these variables in determining anxiety level. This research use quantitative method, description comparison type with factorial design. The population is students at SMAN 3 Padang in XII grade. The samples have chosen with cluster random sampling technique and combined with proportional random sampling technique. The instrument is questionnaire with Likert Scale and tested for validity and reliability. The validity test used Product Moment Correlation and the reliability test used Cronbach's Alpha. Data were analyzed with descriptive statistic technique and varian analyzed (ANOVA). The outcomes shows that: (1) student’s anxiety levels in facing US reviewed by gender, major and ancestry are in high category, (2) there is difference student’s anxiety level between gender, major and ancestry and (3) there is no interaction between gender, major and ancestry in explaining student’s anxiety level in facing US. The implication in counseling can be defined with counseling treatment programme in order to decreasing students’s anxiety level in facing US.Keywords: Anxiety Level in Facing Ujian Sekolah (US), Gender, Major, Ancestry.